2015
DOI: 10.1039/c4cp06118g
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of insoluble polysulfides Li2Sx (x = 1, 2) on Li2S surfaces

Abstract: In lithium-sulfur batteries, the growth of insulating discharge product Li2S film affects the cathode microstructure and the related electron as well as lithium ion transport properties. In this study, chemical reactions of insoluble lithium polysulfides Li2Sx (x = 1, 2) on crystal Li2S substrate are investigated by a first-principles approach. First-principles atomistic thermodynamics predicts that the stoichiometric (111) and (110) surfaces are stable around the operating cell voltage. Li2Sx adsorption is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 43 publications
(48 reference statements)
2
47
0
Order By: Relevance
“…In our earlier work, it was determined that the Li 2 S adsorption energy on the Li 2 S (111) surface is −1.78 eV without the vdW dispersion correction. 50 However stronger adsorption values of −2.25 eV and −2.40 eV are obtained with the vdW-D3 27 and vdW(BJ) 28 approaches, respectively.…”
Section: Electrochemical Performance Of Ccs/s Composite Vs Lithium-mentioning
confidence: 99%
See 2 more Smart Citations
“…In our earlier work, it was determined that the Li 2 S adsorption energy on the Li 2 S (111) surface is −1.78 eV without the vdW dispersion correction. 50 However stronger adsorption values of −2.25 eV and −2.40 eV are obtained with the vdW-D3 27 and vdW(BJ) 28 approaches, respectively.…”
Section: Electrochemical Performance Of Ccs/s Composite Vs Lithium-mentioning
confidence: 99%
“…In Structure-I, the Li-S bond length (Table II) is 0.27 Å shorter than the Li-S bond in the Li 2 S crystal. 50 The length of the short S-S bridge (D S−S ) in Structure-I is 0.35 Å shorter than the S-S distance (4.05 Å) in a typical Li 2 S (110) layer. The variation of these geometric parameters is attributed to the lattice parameter differences between graphene and the Li 2 S (110) layer.…”
Section: Electrochemical Performance Of Ccs/s Composite Vs Lithium-mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Of particular concern to the loss of capacity with cycling is the deposition of electrochemically-inaccessible solid sulfide species (Li 2 S x , x < 3). 4,5 Multiple literature reports have reached different conclusions on the existence of the solid, electrolyte-insoluble species Li 2 S 2 and whether it forms as a solid intermediate during the discharge of Li-S batteries. [5][6][7][8][9][10][11][12] Recent studies have suggested there may be separate reaction pathways that are followed at different points during Li-S discharge: one where only Li 2 S is formed during reduction of soluble polysulfides (Li 2 S x , x > 2), and a second where both Li 2 S and Li 2 S 2 are formed simultaneously.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Recent studies have suggested there may be separate reaction pathways that are followed at different points during Li-S discharge: one where only Li 2 S is formed during reduction of soluble polysulfides (Li 2 S x , x > 2), and a second where both Li 2 S and Li 2 S 2 are formed simultaneously. 11 The question of whether any Li 2 S 2 that forms can then be reduced is debated in the literature.…”
mentioning
confidence: 99%